PANDANGAN MASYARAKAT TERHADAP TRADISI PERHITUNGAN WETON DALAM PERNIKAHAN PERSPEKTIF ‘URF : (Studi Kasus di Ds.Sugihwaras Kec.Ngoro Kab. Jombang) - RIZKA AMALYA MAULIDIA; MASROKHIN (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This thesis aims to find out the public's view of the Weton tradition of calculations in marriage, and also how 'urf views the existence of this tradition. This research is descriptive qualitative research using field or empirical studies. In obtaining data, the author used three data collection techniques, namely observation and documentation of interviews directly from the original source, in this case what is meant is Community Figures, Religious Figures and Ordinary People. Meanwhile, in the analysis used are data collection techniques, data reduction, presentation and drawing conclusions. The research results show that the Javanese people in Sugihwaras Village have a tradition of calculating wedding wetons with the aim of achieving happiness and blessings in life. This tradition is starting to be abandoned by the younger generation, but is still respected and appreciated by most people. This tradition is adapted to Islamic values ​​through comprehensive education and understanding of true Islamic values. The weton calculation tradition is used to choose a soul mate and the wedding day. This tradition is included in the 'urf sahih category, namely habits that are recognized by society and have good intentions. However, this tradition should not be used as the main benchmark in determining your soul mate and wedding day because your soul mate and wedding day are the destiny of Allah SWT. The weton calculation tradition should only be used as a complement and consideration, not an absolute determinant of household happiness. Domestic happiness is determined by effort, prayer and faith in marriage.